Valor nutricional de silagens do capim-tifton 85 em diferentes idades - Wilson Goncalves de Faria Junior (2012)
The objective was to determine the potential of ensilage of Tifton 85 Bermudagrass and indicate the moment of harvest to ensure balance between productivity, nutritional and fermentation quality of silage, intake and protein and energy retention by sheep. The Tifton 85 Bermudagrass was grown at Santa Helena farm, Bom Despacho, MG, between October and December 2007 and was harvested at ages 27, 45, 56, 74 and 90 days of regrowth. There was a variation of dry matter production among the ages and highest production of dry matter and digestible dry matter were observed at 45 days of age (9.2 and 5.9 t/ha). The increasing age of regrowth jeopardized the nutritional quality and fermentation kinetics of the plant. The effects were more pronounced after 74 days. There was a linear decrease in leaf: stem ratio with increasing age (. = 0.7845-0.0041**x, where x is the age of regrowth). The nutritional and fermentation quality of silages were also influenced by the moment of ensiling, with the best fermentative pattern obtained at ages 45 and 56 days. The silage produced at the extremes age (27 and 90 days) showed signs of undesirable fermentation affecting the nutricional protein fraction and dry matter losses. The dry matter intake did not differ between silages (mean of 2.27 g/100g body weight (BW) and 59.04 g/kg BW0.75), but the intake of digestible dry matter was superior to the age of 45 day (29.49 g / kg BW0.75). Nitrogen balance was positive for silage produced at 45, 74 and 90 days of age (3.26, 0.32 and 2.83 g/day, respectively) and urinary losses was the main nitrogen loss. The energy intake was lower and higher, respectively, for the silage produced at 27 days (101.26 kcal/BW0.75) and 45 days (162.19 kcal/BW0.75) regrowth. The silage produced between 45 and 90 days showed similar net energy intake and highest than silage 27 days (89.59 vs. 51.24 kcal/BW0.75), resulting in positive energy balance. Energy losses in urine, methane and caloric increment did not differ between treatments with mean values of 2.43, 4.35 and 14.66 kcal/100kcal gross energy consumed. Methane production was similar between silages (17.33 g/day, 16.90 g/kg dry matter intake). The net energy content of silages was similar, with an average of 1.33 Mcal/kg dry matter. The ensiling of Tifton 85 should occur 45 days of regrowth.